Manajemen Wakaf Produktif dalam Mengembangkan Perekonomian Masyarakat Sekitar Pesantren - Arivatu Ni’mati Rahmatika; Silviana Rini (MARGIN ECO, 2021)
Waqf is included in the category of muamalah teachings where the recommendation to implement it is sunnah. However, waqf has enormous potential in helping to realize the welfare of the people. The purpose of waqf which is to realize the welfare of the people in this case can be realized if the waqf is managed in a productive way. This study aims to determine how waqf management is and to find out how the impact of waqf management on Micro Waqf Bank Bahrul Ulum Barokah Sejahtera Tambakberas Jombang. This research uses qualitative research with using descriptive method. Sources of data in the study obtained through primary and secondary data. The process of collecting data was obtained through observation, interviews, and documentation. Then the data analysis was carried out through several stages, namely data reduction, data presentation, and then drawing conclusions and verification. The results showed that the waqf management in the Micro Waqf Bank Bahrul Ulum Barokah Sejahtera Tambakberas Jombang was managed and distributed productively in the form of business loans with a group system to the community around the pesantren. The perceived impact of waqf management that has been carried out includes aspects of the economy, education and religion. Keywords: micro waqf bank, productive waqf, waqf management